DEVELOPMENT SOFTWARE FOR DMM CALIBRATION, from remote set point until automated reporting - rameli, Mochammad; Iskandar, Eka (JAVA Journal of Electrical and Electronics Engineering, 2016)
Measurement of electrical quantities such as voltage, current, resistance becomes a part in checking the electrical equipment both for industry and households. Digital Multimeter (DMM) can be used as a measurement of electrical quantities. Sometimes the operator can make mistakes such as connecting cable at wrong place, or forgot to change the measurement range so it can break the DMM fuse. Frequent use of calibrator can make text on function button indistinct. DMM calibration should be performed periodically to guarantee the truth values of the results from measurement of electrical quantities. Truth values can be achieved by adding correction value read on DMM. Calculating correction values can be easily done by software and written automatically on certificate of calibration. By involving software in calibration procedure, we can remind the operator when the operator connect the cables at wrong place or forget to change the electrical quantities range with pop up menu that appears on the software. We can generate certificate of calibration automatically from template in which the correction values are calculated.